High-purity lignin fractions and nanospheres rich in phenolic hydroxyl and carboxyl groups isolated with alkaline deep eutectic solvent from wheat straw. (September 2022) - Yue, Xin; Suopajärvi, Terhi; Sun, Shirong; Mankinen, Otto; Mikkelson, Atte; Huttunen, Harri; Komulainen, Sanna; Romakkaniemi, Idamaria; Ahola, Juha; Telkki, Ville-Veikko; Liimatainen, Henrikki
Graphical abstract: Highlights: Alkaline DES consisting of K2 CO3 and glycerol was developed for lignin extraction. Sequential fractionation facilitates the production of high-purity DES lignin. Lignin rich in Ar–OH (9.60 mmol/g) and –COOH groups (2.52 mmol/g) was obtained. Alkaline DES was conducive to reducing the β -O-4 linkages of lignin. Abstract: A combined pretreatment based on alkaline deep eutectic solvent (DES) of K2 CO3 and glycerol and sequential acid fractionation was developed to extract reactive lignin from wheat straw biomass. This process exhibited excellent purification performance in lignin isolation, and the lignin fractionated at low pH displayed high reactivity, having hydroxyl and carboxyl groups up to 9.60 and 2.52 mmol/g, respectively. Silica was selectively separated and removed during the precipitation stage, avoiding the "silica interference". Moreover, DES-lignin nanospheres created by self-assembly using lignin fractions obtained by acid precipitation possessed a high zeta potential, large particle size and high content of hydrophilic groups. Overall, the findings related to the dissociation mechanism and fractionation of reactive lignin during alkaline DES pretreatment and the acid sequence precipitation are crucial for facilitating lignin valorization in high-added value products.